2015
DOI: 10.1002/jca.21394
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of blood exchange transfusion for priapism complicating sickle cell disease

Abstract: Background: Priapism is unwanted painful penile erection that affects about 36% of boys and men with sickle cell disease (SCD) most of whom have sickle cell anemia. Clinically, priapism could be stuttering, minor, or major. The first two types are mild, last < 4 h, are usually treated at home, have good prognosis with normal sexual function. The major type of priapism lasts >4 h, associated with severe pain, requires hospitalization; often does not respond to medical treatment and may require shunt surgery. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 27 publications
2
46
0
2
Order By: Relevance
“…Recurrence rates of 46‐90% are especially concerning. While less commonly performed, other possible indications for scheduled RCE in SCD which appear efficacious include recurrent, severe episodes of acute chest syndrome, vaso‐occlusive pain crises, and priapism . Most patients receiving prophylactic RBC exchanges are maintained on an approximate schedule of exchange every 3‐5 weeks to keep their hemoglobin S (HbS) level below 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rates of 46‐90% are especially concerning. While less commonly performed, other possible indications for scheduled RCE in SCD which appear efficacious include recurrent, severe episodes of acute chest syndrome, vaso‐occlusive pain crises, and priapism . Most patients receiving prophylactic RBC exchanges are maintained on an approximate schedule of exchange every 3‐5 weeks to keep their hemoglobin S (HbS) level below 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the neurologic complications were most likely due to transfusion-induced hyperviscosity. A larger study of blood exchange transfusion in patients with priapism, which maintained the post-exchange Hb level similar to baseline values, showed no neurologic complication in any of the patients [129]. …”
Section: Priapismmentioning
confidence: 74%
“…In a literature review conducted by Kato [16], he found that RCE and other drug treatments were not efficient in this indication and delayed the urologic management. However Ballas and Lyon had obtained clinic regression by cytapheresis by maintaining an HbS rate lower than 30% [17]. …”
Section: Discussionmentioning
confidence: 99%